Steven Test Modeling - Partom, Y. (European Journal of Applied Sciences, 2023)
The Steven test was introduced for studying low velocity impact initiation of explosives. The original diagnostics of the Steven test were blast gauges at a distance of about 3m. Trying to use these diagnostics to characterize the response of the explosive after its ignition, we realized that they’re not informative enough. We therefore replaced the blast gauges by velocity gauges, looking at the free surface of the back plate of the test sample. Our explosive is similar to LX07, and we performed several tests with impact velocities from 30m/s to 122m/s. The velocity histories we obtained from the gauges show the following: 1) there is a rather long delay between impact and ignition (or gauge response), 50µs for the highest impact velocity and around 250 µs for the 36m/s impact; 2) there’s no ignition at the impact velocity of 30m/s; 3) the gauge velocity histories rise gradually to a maximum and then continue with elastic oscillations. We model the response of the explosive assuming that it reacts through shear initiation. The projectile impact causes shear flow in the explosive, which leads to strain localization and formation of shear bands. The shear bands heat up and reach ignition temperature and deflagration waves expand out of them, similar to deflagration waves out of hot spots for shock initiation. Shear initiated reaction rate is rather slow as: 1) shear bands are surfaces (and not spots); and 2) the average distance between shear bands is of the order of 1mm, and not 0.1mm (as for hot spots). Also, shear-initiated reaction rate depends on pressure and not on reactant temperature (as for hot spot initiation). Here we use our PDSR (= Pressure Dependent Shear Reaction) model to reproduce our Steven test data. We get good agreement with delay times and amplitudes of the velocity gauge outputs.